1999
DOI: 10.1088/0741-3335/41/3a/048
|View full text |Cite
|
Sign up to set email alerts
|

Electric field and transport in W7-AS

Abstract: At W7-AS, confinement properties are analysed and compared mainly with neoclassical predictions for quite different conditions. Low-density electron cyclotron resonance heating (ECRH) discharges allow access to the very-long-mean-free-path regime for electrons (T e up to 6 keV) whereas pure neutral beam injections (NBI) and combined NBI/ECRH discharges at high density (T i ≈ T e 1 keV at n e ≈ 10 20 m −3 ) lead to high performance (τ E up to 50 ms). Depending on the achieved temperatures, the experimental tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 18 publications
4
56
0
Order By: Relevance
“…The neoclassically predicted ambipolar radial electric field is generally in agreement with observations in the core of CHS [26] and W7-AS [27,28,29,30] in the 'ion root' regime. Agreement has also been obtained in plasmas with net toroidal current and significant magnetic shear in W7-AS [31], and qualitative agreement has been reported in TJ-II [32].…”
Section: Neoclassical Transport In Stellarators: Theory and Experimentssupporting
confidence: 82%
See 2 more Smart Citations
“…The neoclassically predicted ambipolar radial electric field is generally in agreement with observations in the core of CHS [26] and W7-AS [27,28,29,30] in the 'ion root' regime. Agreement has also been obtained in plasmas with net toroidal current and significant magnetic shear in W7-AS [31], and qualitative agreement has been reported in TJ-II [32].…”
Section: Neoclassical Transport In Stellarators: Theory and Experimentssupporting
confidence: 82%
“…The electron root would be especially valuable in reactors, since the ripple transport has strong temperature dependence. W7-AS experiments have confirmed that transport is reduced by either sign of E r [29]. The electron root is frequently predicted, but often not observed in low-density ECRH plasmas in W7-AS [29] and CHS [34].…”
Section: -9mentioning
confidence: 84%
See 1 more Smart Citation
“…In the stronger ECR-heating plasmas of the Wendelstein-7AS, a centrally peaked profile of electron temperature is observed, and its large electron temperature gradient at a core radius suggests the transport barrier. 71 In contrast to tokamaks, the bifurcation mechanism of the improved confinement regime of the toroidal helical plasmas is simply ascribed to the neoclassical property of the radial electric field. This formation scenario was theoretically expected before its confirmation.…”
Section: Bifurcation and Transport Barriermentioning
confidence: 99%
“…This is because the toroidal flow associated with the ambipolar radial electric field is small compared with the flow due to NBI in most L-mode discharges. In the hot electron mode where the electron thermal transport barrier is established, a large electric field ͑.10 kV͞m͒ appears in the plasma core [20][21][22], then toroidal flow associated with the ambipolar radial electric field may overcome the toroidal flow due to NBI. In this paper, the first observation of toroidal flow antiparallel to the ͗E r 3 B u ͘ drift direction (also antiparallel to the neutral beam injection) near the electron transport barrier in the hot electron mode plasmas is described.…”
mentioning
confidence: 99%